PENGUKURAN KESEHATAN BANK SYARIAH DENGAN SHARIA COMPLIENCE AND PERFORMANCE - Sutrisno Sutrisno (Jurnal Keuangan dan Perbankan, 2017)
The purpose of this study was to measure the health of Islamic banks which were not only based on the financial performance (CAMEL), but also included the performance of sharia. The financial performance was measured by the Capital Adequacy Ratio (CAR), asset quality (NPL), earning Ability (ROA), and liquidity sufficiency (FDR) while sharia performance was measured by education and training grants, profit sharing ratio,  zakah ratio, and Islamic investments ratio. The population in this study were all Islamic banks in Indonesia namely 13 Islamic banks. Furthermore, there were eleven samples of the Islamic banks. It was because there were 2 Islamic banks which were not included in the samples because they officially opened in 2014, so the data had not completed yet. The data in this research was secondary data drawn from the annual financial statements of Islamic banks which had been published. The result showed the contradiction that was banks had high sharia performance, but they had low financial performance.